2013
DOI: 10.1016/j.stem.2012.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Metabolic Flow Enables Large-Scale Purification of Mouse and Human Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Heart disease remains a major cause of death despite advances in medical technology. Heart-regenerative therapy that uses pluripotent stem cells (PSCs) is a potentially promising strategy for patients with heart disease, but the inability to generate highly purified cardiomyocytes in sufficient quantities has been a barrier to realizing this potential. Here, we report a nongenetic method for mass-producing cardiomyocytes from mouse and human PSC derivatives that is based on the marked biochemical differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
763
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 897 publications
(816 citation statements)
references
References 31 publications
12
763
2
2
Order By: Relevance
“…For the following 4 days, cells were cultivated with cardiac basal medium. To enrich the culture for cardiomyocyte-like cells, for the next five days the cells were cultivated in cardiac enrichment medium comprising RPMI1640 without glucose (Gibco) and 4 mM sodium lactate (Sigma-Aldrich) (Tohyama et al, 2013). After enrichment, cells were maintained in cardiac basal medium with medium change every other day.…”
Section: Directed Differentiation Into Cardiomyocytelike Cellsmentioning
confidence: 99%
“…For the following 4 days, cells were cultivated with cardiac basal medium. To enrich the culture for cardiomyocyte-like cells, for the next five days the cells were cultivated in cardiac enrichment medium comprising RPMI1640 without glucose (Gibco) and 4 mM sodium lactate (Sigma-Aldrich) (Tohyama et al, 2013). After enrichment, cells were maintained in cardiac basal medium with medium change every other day.…”
Section: Directed Differentiation Into Cardiomyocytelike Cellsmentioning
confidence: 99%
“…In addition, Shiba et al [20] demonstrated that transplanted human ESC-derived cardiomyocytes electrically coupled to the host cardiomyocytes and suppressed arrhythmias in a guinea pig myocardial infarction model. Furthermore, with respect to cell transplantation in large animals, Kawamura et al [19] recently reported that cardiac cell sheets comprising purified human iPSC-derived cardiomyocytes generated using our method [18] improved cardiac function in a pig myocardial infarction model. Thus, efficacies have been achieved in cell transplantation therapies using human iPSC-derived cardiomyocytes, although many such studies showed only short-term effectiveness.…”
Section: Transplantation Of Human Psc-derived Cardiomyocytesmentioning
confidence: 90%
“…Thus, cardiomyocytes and proliferating noncardiac cells including PSCs showed differences in metabolism (Fig. 4.2) that we then successfully exploited to select cardiomyocytes from human PSCs efficiently and inexpensively simply by changing the cell-specific medium to one that is glucose depleted and lactate supplemented [18]. The cardiomyocytes selected by metabolism showed normal electrophysiological properties and did not form teratoma after transplantation.…”
Section: Nongenetic Methods For Purifying Cardiomyocytesmentioning
confidence: 99%
“…Afterwards, the medium was changed every 3 days. Between day 14 and day 18, cells were selected using lactate as described by Thoyama et al [20].…”
Section: Brought To You By | Mit Librariesmentioning
confidence: 99%